Alih Media Arsip Sebagai Upaya Preservasi Di Dinas Perpustakaan Dan Kearsipan Labuhanbatu Utara - Nazmiah Yusdi Arwana; Abdul Karim Batubara; Muslih Fathurrahman (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the transfer of archival media as a preservation effort. The research method used is a qualitative method with descriptive research that uses interview methods to describe data obtained directly by researchers. The research results show that the media transfer processing process as a preservation effort must use guidelines, namely SOP (standard operational procedure) or media transfer processing workflow issued by the National Archives of the Republic of Indonesia. With this SOP (standard operational procedure), it will be easier for archives to transfer documents. This SOP was prepared to provide guidance or stages in implementing the media transfer process and is expected to make it easier for archivists to carry out the media transfer process. The obstacles/constraints faced in the process of transferring archival media as a preservation effort are the obstacles faced by archivists in processing media transfer collections in a preservation effort, namely the lack of human resources, many archivists in the North Labuhanbatu Library and Archives Service do not yet know about media transfer processing, only 2 archivists who can process transfer of media and also inadequate facilities and infrastructure.